Vaccine safety issues at the turn of the 21st century - Conklin, L; Hviid, A; Orenstein, WA; Pollard, AJ; Wharton, M; Zuber, P (BMJ Publishing Group, 2021)
Global gains in vaccination coverage during the early 21st century have been threatened by the emergence of antivaccination groups that have questioned the effectiveness of vaccines to generate public distrust of vaccines and immunisation programmes. This manuscript summarises six key topics that have been at the centre of global discussions on vaccine safety during the early 21st century: thiomersal in multi-dose non-live vaccines, aluminium adjuvants used with several non-live vaccines, autism and auto-immune conditions as possible consequences of vaccination, a risk of immune overload with increasing numbers of vaccinations, and detrimental non-specific effects (NSEs) of vaccination. For each topic, we describe the hypothesis behind the public concern, the evidence reviewed by the WHO's Global Advisory Committee for Vaccine Safety (GACVS) during 1999-2019, and any significant new data that has emerged since GACVS conclusions were made. Although the scientific evidence on these issues overwhelmingly supports the safety of vaccines, communication messages to caregivers and providers need to condense and convey scientific information in an appropriate way to address concerns contributing to vaccine distrust. In addition, there is need for further studies specifically designed to address both positive and negative NSE of vaccination. The role of GACVS will be increasingly important in evaluating the evidence and engaging the global community in promoting and assuring the safety of vaccines in the decades to come as we move into an era in which we use new vaccination platforms, antigens and formulations.